1979
DOI: 10.1016/0304-4165(79)90222-8
|View full text |Cite
|
Sign up to set email alerts
|

Composition of the aqueous phase of chromaffin granules

Abstract: Nuclear magnetic resonance spectroscopy has been used to determine the composition of the aqueous phase of bovine chromaffin granules. Relative concentrations of catecholamines (epinephrine plus norepinephrine), ATP and chromogranins have been measured from integrated intensities in the proton spectra using computer simulation techniques. Most or all of the catecholamines (97 +/- 8%) are present in the aqueous phase and contribute to the high resolution spectrum. The catecholamine:ATP molar ratio (4.41 +/- 0.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1981
1981
1991
1991

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…(1983aO'Connor et aI. ( ,b, 1984 in human tissues, and offers some support to the contention, based on biochemical evidence presented by Sen et al (1979), that one rfile for chromogranin (specifically chromogranin A) is to stabilize the stored components. containing cells.…”
Section: Discussionmentioning
confidence: 88%
“…(1983aO'Connor et aI. ( ,b, 1984 in human tissues, and offers some support to the contention, based on biochemical evidence presented by Sen et al (1979), that one rfile for chromogranin (specifically chromogranin A) is to stabilize the stored components. containing cells.…”
Section: Discussionmentioning
confidence: 88%
“…It has been suggested that its role is the stabilization of catecholamine-ATP complexes (Pletscher et al, 1974), but n.m.r. studies have provided no evidence that these complexes do in fact exist within the granules (Sharp & Richards, 1977;Sen et al, 1979). Another possibility is that the granules are a reservoir for Ca2+ that penetrates the plasma membrane during the secretory process (Serck-Hanssen & Christiansen, 1973); this is an attractive theory in view of the large number of Abbreviation used: Hepes, 4-(2-hydroxyethyl)-1piperazine-ethanesulphonic acid.…”
mentioning
confidence: 99%
“…The results of fluorescence spectrophotometry (STEFFEN et al, 1974) and NMR spectroscopy (GRANOT and ROSENHECK, 1978;SHARP and RICHARDS, 1977a, b;DANIELS et al, 1978;SHARP and SEN, 1978;SEN et al, 1979) all indicate that the chromaflin granule contents are in a "fluid" or mobile state. In NMR spectroscopy, broadening of absorption bands or decreases in the relaxation rate are associated with a decrease of molecular motion, a condition that does not exist within the chromaffin granule (SHARP and RICHARDS, 1977a, b;DANIELS et al, 1978;SHARP and SEN, 1978;SEN et al, 1979). At the high concentration of solutes within the granule interior, the contents of the chromaffin granule best represent a non-ideal but homogeneous viscous solution (NJUS et al, 1981) (Fig.…”
Section: Role Of Nucleotidesmentioning
confidence: 99%